STUDI EKSEGETIS PERANAN ROH KUDUS DALAM PENGINJILAN BERDASRKAN INJIL YOHANES 16:4B-15 - Waharman Waharman (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
One of the tasks of the church's vocation in this world is to preach the gospel or testify about Christ (Marturia), which is to preach the good news about the salvation of the Lord Jesus to a world filled with sin. That is why every Christian who has received salvation must be His witness in the midst of this world, so that those who do not believe have a part in the kingdom of God in Christ Jesus. But often there is failure and despair by the Evangelists, because they have given all the best efforts in evangelism but there is no soul that believes. This happens one of them because many evangelists do not understand and believe in the role of the Holy Spirit in evangelism. Therefore this article was written to provide an understanding of the role of the Holy Spirit in Evangelism based on the Gospel of John 16: 4b-15.